2-Deoxyglucose Glycolysis Inhibitor Augment Oncolytic Virotherapy to Induce Oxidative Stress and Apoptosis in Breast Cancer (Part Ⅲ) - Obaid, Qayssar A; Khudair, Khalisa K; Al-Shammari, Ahmed M (The Iraqi Journal of Veterinary Medicine, 2021)
One of the "hallmarks of cancer" is altered energy metabolism, which is increased glycolysis in cancer cells, the primary source of energy that uses this metabolic pathway to generate ATP. Oncolytic virotherapy with aerobic glycolysis inhibitor smart therapeutic approach to induce apoptosis in cancer cells. The current study aimed to use the 2-Deoxyglucose (2DG), a specific glycolysis inhibitor, to enhance the Newcastle disease virus (NDV). In this study, a mouse model of breast cancer allograft with mammary adenocarcinoma tumor cells (AN3) was used and treated with 2DG, NDV, and a combination of both. Anti-tumor efficacy and glycolysis analysis (hexokinase -1 (HK-1), pyruvate, and ATP) were determined. The induction of oxidative stress was investigated by reactive oxygen species (ROS) and total glutathione assay examination. Apoptosis induction was investigated using immunohistochemistry (cleaved Caspase-3) and histopathology. The result showed that combination therapy enhances anti-tumor efficacy (decrease in relative tumor volume and increase in tumor growth inhibition) of NDV against breast cancer. This effect was accompanied by a reduction in HK-1 concentration, pyruvate, and ATP (glycolysis products). Moreover, NDV+2DG therapy induces oxidative stress (decreases total glutathione and increases ROS). Immunohistochemistry and histopathological examination showed the apoptotic area in tumor tissues in treated groups. In conclusion, the present study found that the combination therapy could be considered as an effective cancer therapy through induction of glycolysis inhibition, oxidative stress, and apoptosis selectively in cancer cells.